Crystal engineering of palladium terpyridine complexes - Alshgari, Razan (2017)
The ability of 2,2':6',2"-terpyridine (terpy) to chelate to a wide variety of metal ions has led to the synthesis of different metal-terpyridine complexes.In addition, there are different synthetic strategies have been improved, allowing 2,2':6',2"-terpyridine and its derivatives to find a wide range of applications assensors and catalysts. This thesis concerns the synthesis of a series of Pd(terpy) complexes with different para- and meta-substituted pyridine ligands and their properties are studied by X-ray crystallography. In order to extend the experimental observations and the range of applicability of the proposed interpretation, another system involving the tridentate aromatic nitrogen donor 4,4',4''-tri-tert-butyl-2,2':6',2''-terpyridine (tBu3-terpy) has been examined. A range of N,N-bidentate ligandsare introduced in next section. These can be potentially used to bridge two metal centres. The reactivity of [Pd(terpy)(NCCH3)](CF3SO3)2 was investigated with a wide range of N,N-bidentate ligands. Substitution of the acetonitrile ligand of [P(terpy)(NCCH3)](CF3SO3)2 with these ligands was found to be efficient and facile with reactions occurring at room temperature. Extension of this reaction to meso-tetra (4-pyridyl)porphyrin results in tetranuclear Pd(terpy) complex and affords [{Pd(terpy)}4(H2T(4-Py)P)](CF3SO3)8. In Chapter 6, similarly to terpyridine, 2-phenyl-4,6-bis(2-pyridyl)-1,3,5-triazine (pbptz) is coordinated to palladium as a tridentate ligand and no complex was seen to adopt any of the other potential binding modes for this molecule.